Guatteriopsis friesiana W. Rodrigues, nova espécie de Annonaceae para a Amazônia - Rodrigues, William Antônio (Acta Amazonica, 1981)
Guatteriopsis friesiana W. Rodrigues is described as a new species of Annonaceae, which is readily separated from the other 4 species of the same genus especially by its leaves discolour and cordate at the base and in particular from G. kuhlmannii Fries by the outline of its flower buds. A synoptical key for identification of the species of Guatteriopsis is included.